Popliteal pterygium syndrome: case report from rural India - Desai, Vasav D.; Desai, Gayatri S.; Raulji, Nirav (International Journal of Contemporary Pediatrics, 2020)
The popliteal pterygium syndrome is a congenital malformation that includes orofacial, musculoskeletal and genitourinary anomalies. It is also known as faciogenitopopliteal syndrome. It is autosomal dominant disorder. It has highly variable expressivity and incomplete penetrance. The incidence of the popliteal pterygium syndrome is 1/300000, which makes it an extremely rare condition. The most striking characteristic of this syndrome is popliteal pterygium, which consists of a net of connective tissue spreading from the ischial tuberosity to the calcaneus.In this study, authors present the case of a 1 day old male patient with cleft upper lip, cleft palate, bifid scrotum, popliteal pterygium and congenital talipes equinovarus (CTEV).